Intra- and inter-observer reliability of girth measurements of the neck, chest, and abdomen in dogs - Söder, Josefin; Ehnberg, Ludvig; Löfberg, Erica; Höglund, Katja; Bergh, Anna (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aimed to assess intra- and inter-observer reliability of neck, chest, and abdominal girth measurements in dogs and to compare these measurements made with a measuring tape, equipped with or without a dynamometer.MethodsThe locations of the middle neck, cranial and widest chest, and cranial and caudal abdomen were measured individually by two observers in 16 dogs standing squarely at an examination table. Girth measurements were performed in triplicate with the other observer recording the data. All dogs underwent evaluation using a measuring tape equipped with a spring dynamometer, while a subgroup (n = 8) was also evaluated with a measuring tape without the dynamometer. Intraclass correlation coefficients (ICCs), with a 95% confidence interval (CI), were computed to assess the intra- and inter-observer reliability for the measurements made with the measuring tape equipped with a spring dynamometer. Pearson’s correlations (r) were used to compare the two methods: girth measurements performed with and without the dynamometer.ResultsGirth measurements at all locations demonstrated high intra-observer (0.967–0.999) and inter-observer (0.985–0.995) reliability. The correlations between measurements made with and without the dynamometer were high (r ≥ 0.996, p < 0.0001). Numerically higher girth values with numerically lower precision were recorded using the tape measure without the dynamometer, but only the girth of the cranial abdomen differed significantly between methods (p = 0.04).Conclusion and clinical importanceGirth measurements were reliable across all locations, particularly in the cranial chest and caudal abdomen, which exhibited high precision both within and between the two observers. A tape measure loaded with a dynamometer is recommended, as measurements recorded with a tape measure only showed a tendency of higher girth values with lower precision. Future research should evaluate neck, chest, and abdominal girth measurements in overweight canine patients, as well as the usefulness of the method as a complement to clinical body condition assessment for tracking changes in body composition.